Calculation of mental load from e-learning student with NASA TLX and SOFI method - Febiyani, Anastasia; Febriani, Atik; Ma'Sum, Jauhar (Universitas Serang Raya, 2021)
The learning process between students and lecturers usually occurs face-to-face in class. Technological developments and a continuous pandemic change the learning process to be a face-to-face e-learning process. The mental load during face-to-face learning is very different from learning in e-learning. This study was built using ergonomic thinking that is integrated with the use of e-learning. Cognitive ergonomics see from the point of view of students' comfort in cognitive thinking processes when doing e-learning. Data processing and testing will use a questionnaire derived from the NASA-TLX method. The results obtained from this study are the mental load calculations of each NASA TLX calculation. NASA TLX calculations show that efforts with a value of 267.29 dominate students. It could indicate that in e-learning lectures, students need more effort in conducting lectures. In addition, students experience fatigue while participating in online learning. It can be seen from the average SOFI measurement, which is only 1.26.